Attitude of Farmers Towards Use of Combine Harvester - Lambe, S. P. , P. K. Wakle and A. S. Gomase (Indian Journal of Extension Education, 2014)
The present study was undertaken in Akola district of Maharashtra State. An exploratory design of social research wasused. A sample of 100 farmers who harvested their crop with the help of combine harvester were drawn and informationwas collected which was considered for tabulation and analysis of the data. The farmers who used combine harvester werein middle age group (45.00%), educated up to high school level (48.00 %) and possessed large land holding (50.00%).Half of the respondents possessed the hand operated and bullock drawn implements. Very few of them possessed thepower operated implements. In case of attitude, the farmers showed the favorable attitude (65.00%) towards the use ofcombine harvester.